Optimization of a FBG-based filtering module for a 40 Gb/s OSSB transmission system - Drummond, Miguel V.; Ferreira, Artur; Silveira, Tiago; Fonseca, Daniel; Nogueira, Rogério N.; Monteiro, Paulo (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
We present the optimization of an optical filtering module (OFM) of a single-channel 40 Gb/s transmission system with optical single-sideband modulation and alternate mark inversion signaling. Sideband suppression and dispersion compensation are simultaneously performed by the fiber Bragg grating (FBG) optical filtering through amplitude and phase response, respectively. Different amounts of accumulated dispersion are compensated using an OFM based on optical switches and chirped FBGs with different accumulated dispersion. Linear transmission simulations to assess the OFM effectiveness yield a Q-factor penalty variation lower than 1 dB relative to back-to-back considering a maximum accumulated dispersion of 20400 ps/nm. A transmission distance of 1040 km of nonlinear standard single mode fiber is achieved with a Q-factor higher than 7.
Optica Applicata, Vol. 40, 2010, nr 2, s. 511-520
Keywords: optyka; optical single sideband (OSSB); alternate mark inversion (AMI); dispersion compensation (DC); fiber Bragg gratings (FBG)